Oscillator circuits : frontiers in design, analysis and applications - Nishio, Yoshifumi (Materials, circuits and devices series, 2016)
An electronic oscillator is an electronic circuit that produces a periodic (often a sine wave, a square wave, or a pulse trains) or a non-periodic (a double-mode wave or a chaotic wave) oscillating electronic signal. Oscillators convert direct current from a power supply to an alternating current signal, and are widely used in many electronic devices. This book surveys recent developments in the design, analysis and applications of this important class of circuits. Topics covered include an introduction to recent developments; analysis of bifurcation in oscillatory circuits; fractional-order oscillators; memristive and memcapacitive astable multivibrators; piecewise-constant oscillators and their applications; master-slave synchronization of hysteresis neural-type oscillators; multimode oscillations in coupled hard-oscillators; wave propagation of phase difference in coupled oscillator arrays; coupled oscillator networks with frustration; graph comparison and synchronization in complex networks; experimental studies on reconfigurable network of chaotic oscillators; fundamental operation and design of high-frequency tuned power oscillator; ring oscillators and self-timed rings in true random number generators; and attacking on-chip oscillators in cryptographic applications. Providing an overview of the state-of-the-art in oscillator circuits, this book is essential reading for researchers, advanced students and circuit designers working in circuit theory and modelling, especially nonlinear circuit engineering.